Penerapan Hygiene dan Sanitasi di Laboratorium dan Optik ARO Gapopin - Murni Marlina Simarmata; Nisa Umami Zakiati; Meisha Azharany (Akademi Refraksi Optisi dan Optometry Gapopin, 2022)
This study was aimed at describing and at assessing the implementation of hygiene and sanitation in ARO Gapopin Laboratories and Optical. The research employed qualitative method and comparative study. Data gained through observation were compared to data gained from documentary and literature study. The results indicate that the implementation of hygiene and sanitation in the laboratory and optic is good as students and lecturers always obey SOP and the wastes are managed well. Sanitation and hygiene are crucial for everyone, especially for those who work in laboratory and optical.